Lercanidipine in patients with chronic renal failure: the ZAFRA Study - N. R. Robles; J. Ocon; C. F. Gomez; M. Manjon; L. Pastor; J. Herrera; J. Villatoro; J. Calls; J. Torrijos; V. I. Rodríguez; M. M. A. Rodriguez; M. L. Mendez; et al. (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To evaluate the safe use of a new calcium channel blocker, lercanidipine, in patients with chronic renal failure (CRF); the protective effect of calcium channel blocker on renal function in CRF patients previously treated with ACE inhibitors or angiotensin receptor blockers (ARB). Material and methods. The study included 203 CRF patients (creatinine >1,4 mg/dL for men, >1,2 mg/dL for women; or creatinine clearance <70 mL/min). All patients were receiving ACE inhibitors (63,4 %) or angiotensin II antagonist (36,6 %) therapy, but they had higher blood pressure than recommended for CRF (130/85 mmHg). No patients received diuretics. Patients were clinically evaluated 1, 3, and 6 months after starting treatment with lercanidipine. Urine and blood samples were taken during the examination. When needed, a third drug was added to the treatment, excluding diuretics. Creatinine clearance was measured using 24 h urine collection. Results. 175 patients completed the study protocol (age 63,9±11,9 years, 52,9 % males and 47,1 % females). Blood pressure (BP) significantly decreased from 162±17/93±8.3 mm Hg to 132±12/78±6 mm Hg. 89,2 % of patients showed a significant BP reduction, and 58,1 % achieved optimal BP control (<130/85 mmHg). Seven patients (3,4 %) showed adverse effects. No single case of oedema was detected, and the prevalence of adverse effects related to vasodilatation was extremely low (3 patients, 1,48 %). Plasmatic creatinine did not change (1,9±0,5 baseline vs.1,9±0,6 mg/dL), but creatinine clearance increased at the end visit (41,8±16,0 baseline vs. 45,8±18,0 mL/min, p=0,019). Plasmatic cholesterol also decreased from 221±46 to 211±35 mg/dL (p=0,001). Conclusion: Lercanidipine showed a high antihypertensive effect in CRF patients. It had a good tolerability profile and showed an interesting effect on plasmatic lipids. An improvement in renal function, assessed by creatinine clearance, was detected.